Transcriptome-Wide Analyses Identify Dominant as the Predominantly Non-Conservative Alternative Splicing Inheritance Patterns in F1 Chickens - Qi, Xin; Gu, Hongchang; Qu, Lujiang (Frontiers in Genetics, 2021)
Transcriptome analysis has been used to investigate many economically traits in chickens; however, alternative splicing still lacks a systematic method of study that is able to promote proteome diversity, and fine-tune expression dynamics. Hybridization has been widely utilized in chicken breeding due to the resulting heterosis, but the dynamic changes in alternative splicing during this process are significant yet unclear. In this study, we performed a reciprocal crossing experiment involving the White Leghorn and Cornish Game chicken breeds which exhibit major differences in body size and reproductive traits, and conducted RNA sequencing of the brain, muscle, and liver tissues to identify the inheritance patterns. A total of 40 515 and 42 612 events were respectively detected in the brain and muscle tissues, with 39 843 observed in the liver; 2807, 4242, and 4538 events significantly different between two breeds were identified in the brain, muscle, and liver tissues, respectively. The hierarchical cluster of tissues from different tissues from all crosses, based on the alternative splicing profiles, suggests high tissue and strain specificity. Furthermore, a comparison between parental strains and hybrid crosses indicated that over one-third of alternative splicing genes showed conserved patterns in all three tissues, while the second prevalent pattern was non-additive, which included both dominant and transgressive patterns; this meant that the dominant pattern plays a more important role than suppression. Our study provides an overview of the inheritance patterns of alternative splicing in layer and broiler chickens, to better understand post-transcriptional regulation during hybridization.